2009
DOI: 10.1523/jneurosci.0957-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Fate and Phenotype Specification of Cerebellar GABAergic Interneurons

Abstract: In most CNS regions, the variety of inhibitory interneurons originates from separate pools of progenitors residing in discrete germinal domains, where they become committed to specific phenotypes and positions during their last mitosis. We show here that GABAergic interneurons of the rodent cerebellum are generated through a different mechanism. Progenitors for these interneurons delaminate from the ventricular neuroepithelium of the embryonic cerebellar primordium and continue to proliferate in the prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
158
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(173 citation statements)
references
References 63 publications
8
158
2
2
Order By: Relevance
“…Although the genesis of most cerebellar cell types occurs very early from the periventricular neuroepithelium lining the fourth ventricle, interneurons complete their centrifugal migration through the white matter and their specification postnatally (Maricich and Herrup 1999). Yet, this is not just a migratory event because cell proliferation of the progenitors still occurs in prospective white matter (Leto et al 2009), thus assuming features of a protracted, parenchymal cell genesis. In addition, the postnatal mammalian cerebellum undergoes a genesis of granule cells through a transitory, secondary germinative layer localized on its surface (the external germinal layer [EGL]).…”
Section: Postnatal Extension Of Embryonic Neurogenesis: Possible Overmentioning
confidence: 99%
“…Although the genesis of most cerebellar cell types occurs very early from the periventricular neuroepithelium lining the fourth ventricle, interneurons complete their centrifugal migration through the white matter and their specification postnatally (Maricich and Herrup 1999). Yet, this is not just a migratory event because cell proliferation of the progenitors still occurs in prospective white matter (Leto et al 2009), thus assuming features of a protracted, parenchymal cell genesis. In addition, the postnatal mammalian cerebellum undergoes a genesis of granule cells through a transitory, secondary germinative layer localized on its surface (the external germinal layer [EGL]).…”
Section: Postnatal Extension Of Embryonic Neurogenesis: Possible Overmentioning
confidence: 99%
“…DCN interneurons and Golgi, Lugaro, basket, and stellate cells of the cortex originate in sequential, overlapping phases from progenitors that maintain multipotency throughout the prolonged period of interneuron cell genesis (Maricich and Herrup, 1999;Leto et al, 2006). A variety of cell and tissue transplantation approaches has shown that terminal differentiation state is directed by local cues (Leto et al, 2006) and that the microenvironment of the WM provides critical cell fate cues (Leto et al, 2009). Our observation of transient and dynamic Ngn1 expression in interneuron precursors in the WM raises the possibility these cues could be mediated through Ngn1 activity.…”
Section: Ngn1 Expression In Gabaergic Interneuron Cell Lineages Of Thmentioning
confidence: 99%
“…GABAergic interneurons are generated in defined but overlapping stages and interneuron cell types become specified in an overlapping, inside-out sequence: DCN interneurons are the first to differentiate (beginning E14.5), followed by those of the overlying cortex (E16.5 onward) that differentiate in a progression from those of the inner granule cell layer to the outer-most molecular layer (Leto et al, 2006(Leto et al, , 2009. During development, mitotic interneuron progenitors migrate to the WM as the VZ disappears.…”
Section: Introductionmentioning
confidence: 99%
“…The different types of GABAergic interneurons of the cerebellar cortex and nuclei derive from a common pool of multipotent progenitors (Leto et al, 2006), which upregulate the transcription factor Pax2 during their last mitosis (Weisheit et al, 2006;Leto et al, 2009). These progenitors originate from the medial region of the cerebellar ventricular neuroepithelium (VN) (Mizuhara et al, 2010), but delaminate to the prospective white matter (PWM), where they continue to divide up to postnatal development (Zhang and Goldman, 1996;Maricich and Herrup, 1999;Milosevic and Goldman, 2002).…”
Section: Introductionmentioning
confidence: 99%